The Nominative Object in Slavic, Baltic, and West Finnic - Timberlake, Alan (Slavistische Beitraege, 1974)
This work is the investigation of a single problem in syntax and grammatical categories. Because of the nature of the particular problem, the work is necessarily synchronic and diachronic in approach.